Comprehensive assessment of the geological heterogeneity of reservoir systems in the process of regulating the development of oil fields - Yuri A. Kotenev; Shamil Kh. Sultanov; Alexander V. Chibisov; Viktor M. Chilikin (Нанотехнологии в строительстве)
Introduction. Today, a detailed study of the geological structure of oil and gas fields is essential. The study and understanding of the geological structure can be achieved through the analysis of geological heterogeneity. This has a significant impact on the degree of involvement of the reservoir volume in the drainage process, determines the dominant directions of filtration flows and the nature of oil displacement in the process of formation flooding. Methods and materials. The paper presents statistical indicators of the main reservoir characteristics – porosity, permeability, dissection, sandiness, as well as complex indicators of macro- and microheterogeneity in permeability distribution. The given characteristics allow estimating the variability of the reservoir, both by area and by section, i.e. in the volume of the oil-and-gas bearing reservoir. Results. This paper highlights the results of a comprehensive analysis of the micro- and macroheterogeneity of the studied object and a comparison of the identified zones with production data on well operation. The purpose of the study is to develop, using the example of studying the UV1 formation, an algorithm for selecting geological and technological measures, including the use of horizontal well drilling with aphron-containing drilling muds, based on identifying geological and industrial causes of premature water cut in the extracted products, and determining the geological factors that control the distribution of residual hydrocarbon reserves. Determining the causes of premature water cut will help not only to eliminate premature water cut, but also to carry out work to prevent it. Conclusion. The established causes of premature well water cuttings as a result of the analysis will allow to determine promising areas for optimizing the development system – revision of the well grid, drilling of new horizontal production and injection wells, changing operating modes, using flow-diverting technologies, etc. Establishing the directions of fluid movement using heterogeneity analysis helps to determine the sources of water that prematurely enters the well (bottom or injected waters).